O cinema audiovisual: um formato configurado na interação teatro/cinema e TV - Luz, Inez Pereira da (2007)
The culture of the audiovisual has since 1980 been expanding as a circulating space for a set of old and new creative expressions. This movement promotes significant changes in the practices within the systems of signs and means, originating new formats whose compositions unveil the convergence of languages, regardless of the means which originate them and where they are inserted in. We start out from the hypothesis that the current Brazilian cinema is part of the audiovisual culture dynamics as a productive sphere where the hybridity of techniques and languages is predominant and, as a whole, the movement of feature films is not restricted to movie theater rooms, but rather flows through the space as a net, along with other audiovisual formats. The corpus of the research is formed by a few films made in Brazil between 1994/2004, resulting from the interaction cinema/TV and theater, and our objective was to survey the updating process of those expressions in their language compositions. Our method of analysis originates from the interlacing of the theories of I. Lotman (1996-1969), Jacques Aumont (2003, 2004), Noel Burch (1969), Gilles Deleuze (1990), M. McLuhan (1911-1980) and Umberto Eco (1987). Some of them point to languages as productions that are born from dialectical languages between the technical development and the cultural universe that shelters them, promoting the advances and ruptures of the systems of signs, from the aesthetics perspective and the knowledge production. Our research starts with some films shot by modern moviemakers, Orson Welles and Jean-Luc Godard, where we identify a thinking and a method on language interaction. We see how present they are in some contemporary formats created for the circulation in the TV medium. In the composition assessment of the film language of our corpus, we saw that they recreate the uniqueness of the systems of signs that originate them, mingling visual and audio references while the word is treated as a body where multiple expressions of literature, TV, comics, theater and songs are embedded. When making their sets visible, the films convey the creative process and one of the contemporary culture and thought perceptions, a writing that expands the dialogic thinking of cultural practices. The audiovisual formats configured by TV/cinema media to circulate in the network spaces bring in the pragmatic expression of the language, evidencing its extreme importance for the contemporary culture